Young Children’s Inductive Inferences Within Animals Are Affected by Whether Animals Are Presented Anthropomorphically in Films - Tarłowski, Andrzej; Rybska, Eliza (Frontiers in Psychology, 2021)
At the present day, most children are exposed to anthropomorphized animals in a variety of contexts. The growing literature that analyzes this phenomenon suggests that anthropomorphic media exposure may strengthen children’s anthropocentric representation of animals. There is a yet unexplored difference between anthropomorphized and realistic depictions of multiple animal species presented simultaneously in a film. The anthropomorphized animals all behave like humans so they are more behaviorally similar to one another than animals depicted realistically. We asked whether witnessing multiple species of animals depicted anthropomorphically or realistically influences the way 5-year-old children perceive internal commonalities among animals. One group of children watched a cartoon presenting multiple species of anthropomorphized animals, the other group watched a realistic nature documentary also presenting multiple species. Both groups extended a novel internal feature from an animal to a variety of items including diverse animal species. Children watching a cartoon made significantly stronger projections to nonhuman animals than children watching the documentary. Children’s projections to humans and inanimates did not differ between the groups and were uniformly low. One of the possible explanations of the results is in terms of children’s essentialist expectation that behavior is caused by internal properties.